Colombian Consensus defining the criteria for admission of critically ill pregnant patients to the intensive care unit. A document aimed at reducing variability in the care provided to pregnant women with severe complications - Hernando Gaitán-Duarte (Federación Colombiana de Obstetricia y Ginecología, 2014)
Extreme maternal mortality and morbidity continue to be a serious public health issue in Colombia. In order to address this problem, it is essential to make an early diagnosis of severe pregnancy complications, provide initial management, ensure timely referral of patients with severe preeclampsia, post-partum bleeding, obstetric infection, pulmonary embolism and other pathologies with a poor prognosis when associated with pregnancy, delivery and post-partum, and which require a multidisciplinary approach in critical care units. For this reason, although it is not the policy of Revista Colombiana de Obstetricia y Ginecología (RCOG) to publish manuscripts already brought to the public by other media, we have decided to publish the Clinical Practice Guidelines for prenatal control and management of partum and post-partum complications, as well as the Guidelines for the syndromic management of genital tract infections published by the Colombian Ministry of Health and Social Protection. The aim is to disseminate the recommendations for the management of pregnant women with severe complications among Obstetrics and Gynaecology specialists, general practitioners, and nurses practicing obstetrics in Colombia. Consequently, this issue of RCOG includes the "Consenso colombiano para la definición de los criterios de ingreso a unidades de cuidados intensivos en la paciente embarazada críticamente enferma" (Colombian Consensus defining the criteria for admission of critically-ill pregnant women to the intensive care unit). This management guideline was published in September 2013 in Acta Colombiana de Cuidado Intensivo, vol. 13, supl. 5. In this way, we hope to contribute to the reduction of maternal mortality in Colombia.